Why has the caesarean rate increased dramatically in Bangladesh?. (12th November 2019) - Huda, N.; Richards, J.; Rahman, L.; Syed, S.
Abstract : Objective: The objective is to assess the reasoning by families in deciding between a home vs. facility delivery and vaginal vs. caesarean. Study design: The authors selected a convenience sample of 16 villages in Sathkira district in southwest Bangladesh. Evidence was drawn from detailed in‐home post‐delivery interviews with all mothers in these villages who delivered in 2015 or 2016. Methods: Local family health workers and paramedics used a structured questionnaire that enabled gathering of relevant quantitative and qualitative evidence. Mothers' reasons for selection of delivery location and type were categorized, and regression analysis was conducted to assess significance of variables that proxy supply and demand factors. Results: Among 492 completed interviews, 48% were home deliveries, 52% facility deliveries; two‐thirds of facility deliveries in private clinics. Overall, sample caesarean rate is 39%, public hospital rate 53%, private clinic rate 86%. Over half of reasons for home delivery refer to pregnancy without complication or access to trusted birth attendant. Over half of reasons for facility delivery refer to medical complications allegedly precluding home delivery, or requiring home‐to‐facility transfer during labour for reasons not clear to the mother. The decision depends on both 'demand' factors originating with the family (proxied by family income, birth order and education levels) and 'supply' factors originating with obstetric care providers (proxied by number of antenatal visits and variation of caesarean rate by village). In a regression controlling for both demand and supply variables, the above proxy variables are all significant. Implications for nursing and health policy: Bangladesh has inadequate nursing support for vaginal delivery in either home or facility. Hence, physicians frequently recommend that women deliver in a facility (usually a physician's clinic). Physicians are reluctant to hire adequate nurses to attend vaginal deliveries. Hence, families with some discretionary income are increasingly opting for a caesarean over vaginal delivery. Facility deliveries reduce incidence of obstructed labour fistula, but probably contribute to rising incidence of iatrogenic fistula. Reducing caesarean rates requires a large increase in numbers of nurses and midwives, and acceptance by physicians of a broad scope of practice for nurses/midwives in vaginal deliveries.